The dynamics of occupational segregation in comparative context - Fagan, Colette [Verfasser]; Rubery, Jill [Verfasser]; Beckmann, Petra [Herausgeber] (My University, 1996)
The Reskin and Ross (1990, Reskin 1994) model of the job queue and the gender queue provides a dynamic conception of the processes of gender segregation, desegregation and resegregation. This paper argues that when the Reskin and Roos model is applied to cross- national rather than single country studies it has to be adapted to integrate national variation in institutional systems and labour market conditions. This modification of the model sensities the analysis to different processes of change and different outcomes which coexist with broadly similar trends in the pattern of occupational segregation across the European Union. (Autorenreferat)
Keywords: G 2.4.5 Gender Mainstreaming; T 2 Theoretische Ansätze; G 1.2.3 Qualifikationsentwicklungen; G 2.3.4 Qualifikationswandel; G 2.3 Wandel von Arbeit & Wirtschaft; G 1.2.2.2 Soziale Sicherungssysteme; G 1.2 Arbeitsmarkt; I 2.2 Europa; Segregation; Internationaler Vergleich; Geschlechtsspezifischer Arbeitsmarkt; Berufsstruktur; Arbeitsmarkttheorie; Modell; Berufswandel; Tätigkeitswandel; Soziales System; Beschäftigungssystem; Quantitative Angaben; Europäische Union